2020
DOI: 10.1097/tp.0000000000002803
|View full text |Cite
|
Sign up to set email alerts
|

An Outpatient Hospital-based Exercise Training Program for Patients With Cirrhotic Liver Disease Awaiting Transplantation: A Feasibility Trial

Abstract: Background. Time spent on the waiting list before liver transplantation (LT) provides an opportunity to optimize recipient fitness through prehabilitation, potentially reducing the physiological impact of major surgery. We assessed the feasibility and effectiveness of a 6-week exercise program in patients with cirrhotic liver disease awaiting LT. Methods. This single-center, prospective cohort, feasibility study, enrolled patients awaiting LT to a 6-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(109 citation statements)
references
References 28 publications
1
94
0
Order By: Relevance
“…This was also observed in an earlier Canadian pilot RCT [113]. A study from the UK showing the feasibility of a hospital-based training program offered structured nutritional advice in both arms based on the EASL recommendations [114]. Two studies have also demonstrated a beneficial effect of a combined nutritional and PE intervention on portal pressure [115•, 116].…”
Section: Combining Nutritional Interventions With Physical Exercisementioning
confidence: 61%
“…This was also observed in an earlier Canadian pilot RCT [113]. A study from the UK showing the feasibility of a hospital-based training program offered structured nutritional advice in both arms based on the EASL recommendations [114]. Two studies have also demonstrated a beneficial effect of a combined nutritional and PE intervention on portal pressure [115•, 116].…”
Section: Combining Nutritional Interventions With Physical Exercisementioning
confidence: 61%
“…It remains unknown whether an improvement of 1.7ml/kg/min VO 2 peak is clinically meaningful in CLD. Morkane et al reported that, while the intervention group increased their VO 2 peak by +2.3 mL/kg/min following a 6 week thrice weekly cycle ergometry exercise, the control group decreased their VO 2 peak by 1.9 mL/kg/min. The latter deterioration is not surprising in light of the fact that all participants had progressive decompensated liver disease, requiring liver transplantation.…”
Section: Physical Exercise In Patients With Chronic Liver Diseasementioning
confidence: 99%
“…Reassuringly, however the Italian SportDiet study of 50 patients with compensated cirrhosis highlighted that 16-weeks diet and exercise intervention was both safe and significantly reduced portal pressures [80•]. To date, eleven studies (5 RCT, 5 observational, 1 case report) have demonstrated that exercise improves anaerobic thresholds, peak VO 2 , 6MWD, muscle mass/function and to a certain extent quality of life in patients with compensated and decompensated cirrhosis [62,[81][82][83]. None of these studies investigated survival benefit and the majority were small (1-50 patients), focus on supervised, hospital-based aerobic exercise interventions (i.e.…”
Section: Exercisementioning
confidence: 99%